Improving The Ability Of Writing Exposition Text Using Discovery Learning Learning Model Class VIII Students Of SMP Negeri 5 Mandrehe Study Year 2020/2021 - Theodorius Bastian Gulo (UMSU, 2021)
This research was motivated by the existence of problems in learning to write that occurred in junior high schools, especially in writing exposition texts. The purpose of this study was to determine the increase in the ability to write an exposition text using the discovery learning model of class VIII students at SMP Negeri 5 Mandrehe. The method used in this research is designed with classroom action research. The results showed that the students' exposition writing ability using discovery learning method had a significant increase. Judging from the increasing average results of students, it can be concluded that the use of the Discovery Learning method is suitable for learning to write exposition text.